Effective probiotic regimens for bacterial vaginosis treatment and recurrence prevention: A systematic review - Udjianto, Udjianto; Sirat, Noorhamdani A.; Rahardjo, Bambang; Zuhriyah, Lilik (Narra Sains Indonesia, 2025)
Probiotics represent a promising alternative therapy for bacterial vaginosis; however, consensus on the most effective species, strains, and doses remains lacking, and long-term safety data are limited. The aim of this study was to evaluate the effectiveness of probiotics in managing bacterial vaginosis, considering species, strain, clinical outcomes, optimal dosage, duration, and side effects. This study included randomized-controlled trials (RCTs) published in English (2014–2024) on probiotic treatment for bacterial vaginosis, assessing species, strain, dose, duration, and efficacy. A systematic search was conducted on December 20, 2024, in Scopus, Web of Science, and PubMed using the keywords